Torque and back-emf in hybrid excited claw pole generator. Issue 4 (17th August 2018) - Wardach, Marcin
Abstract : Purpose: The paper aims to present the hybrid excited claw pole generator design, simulation and experimental results. The prototype has claw poles on two rotor sections, between which an excitation coil is located. The innovation of this machine is permanent magnets location on claws of one part of the rotor. The paper presents construction of the machine and analysis of the current in the excitation control coil influence on the electromagnetic torque, cogging torque and back-emf values. Presented studies enabled the determination of the torque and the back-emf for both: the strengthening and the weakening of magnetic field. Design/methodology/approach: In the study, finite element analysis was used to perform simulation research. Then, based on the simulation studies, an experimental model was built. The paper also presents selected experimental results. Findings: Achieved results show that the proposed machine topology allows to eliminate the disadvantages mentioned in paper, i.e. necessary to introduce special areas inside the machine to limit magnetic flux leakage or its complicated construction. Research limitations/implications: The obtained cogging torque values and back-emf pulsation are still relatively high. In the near future, some of known techniques for reducing these pulsations can be applied, including the use of magnetic wedges, changing shapes of rotor's poles and/or skewing of permanent magnets. Practical implications: The proposed solution can be used in wind turbines as a generator. Originality/value: The paper presents an original design of a new construction of a hybrid-excited claw pole machine and also an excitation current influence on cogging torque and back-emf values.